The THE EFFECT OF MUDHARABAH FINANCING ON THE ROA (RETURN ON ASSET) IN SHARIA COMMERCIAL BANKS FOR THE PERIOD 2014-2019 - Sholihah, Imro’atus; Salwa, Alivia Meisda; Rabbani, Didin Burhanuddin (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2021)
The development of the sharia economy in Indonesia continues to experience rapid development, especially in the banking sector. Where the banking world is given a great opportunity by the government to carry out its business activities based on sharia principles. As a financial institution, Islamic banks must have differences with conventional banks, especially in terms of financing. Islamic banks are more focused on financing with the principle of profit sharing which is expected to be able to meet the criteria of liquidity, profitability, and solvency. To achieve high profitability, funds are required in appropriate financing. One of the ratios to measure the level of profitability is the Return On Asset (ROA) ratio. The purpose of this study is to determine whether there is an effect of Mudharabah financing on ROA generated by Islamic Commercial Banks for the 2014-2019 Period. This research method is included in the type of quantitative research with an associative approach. Population is taken from the annual report of 14 Islamic Commercial Banks. The sampling technique used simple random sampling. The research sample was obtained in the form of the annual financial reports of 5 Islamic Commercial Banks for the period 2014-2019. Where the data collection uses secondary data obtained from the Banking Statistic Report published by the Financial Services Authority (OJK) and the annual Financial Report published by each Islamic Commercial Bank. The results of testing the regression coefficients by coefficients obtained the sig value of mudharabah financing of 0.717 > 0.05. This means that the independent variable mudharabah has no significant effect on the dependent variable Return on Assets (ROA). So this shows that Ho is accepted and Ha is rejected, with the conclusion that partially mudharabah financing has no significant effect on the Return on Assets (ROA) of Islamic Commercial Banks for the 2014-2019 period.